Review on development and application of 4D-printing technology in smart textiles - Li, Shuai (Journal of engineered fibers and fabrics, 2023)
4D printed products can change shape under external stimulation, and the deformation design of material and structure is directly built into the material, which simplifies the manufacturing process from design concept to physical object and allows the object to be automatically assembled and conformed, realizing the integration of product design, manufacturing, and assembly. In recent years, 4D printing technology has also received widespread attention in the smart textile industry. This paper aims to promote the diversified and efficient development of the smart textile industry and expand the scope of the application of additive manufacturing technology. First, the evolution of 4D printing and its intrinsic relationship with 3D printing are examined. Then, the types of 4D printing smart textile technologies and their characteristics are presented, and the influence of relevant parameters of each type of technology on the molding quality, deformation mechanism, and driving performance of printed models is discussed. Materials for 4D printing of smart textiles are further described, including shape memory materials, hydrogels, and elastic liquid crystals. To adapt to the specific properties of textile applications, 4D printing technology has developed from the structural level of textiles to create smart textiles with adjustable shapes, properties, or functions. Then, the applications of 4D printed smart textiles in different fields are summarized. Finally, some problems currently faced by 4D printed smart textiles are discussed, and their prospects are projected.